Studies of productivity, immunocompetence and genetic diversity of naked neck and normal feathered indigenous Cameroon and German Dehlem Red Fowl and their crosses - Joseph, M.M. (1995)
The trial was started by importing GDR chicken from Humboldt University of Berlin, Germany and indigenous Cameroon fowl by collecting eggs from villages in the Western highland area of Cameroon hatched at the Institute of Animal and Veterinary Research, Mankon (Cameroon). The males of the base population were subjected to fattening test (body weight performance) up to 12 weeks of age. Approximately 10 percent of the birds were slaughtered at 12 weeks of age to determine gizzard, feet, head, liver, heart and dressed yield as the percent of the liveweight. The hen were tested for egg production up to 72 weeks of age and traits such as egg number, body weight at 20, 30, 36, 42, and 72 weeks, shank length at 20, 30 and 42 weeks, egg quality, survival age, age at sexual maturity, feed intake and abdominal fat were measured. First generation chicks were then produced by mating the parent generation using artificial insemination to produce a stock which comprised of eight genotype groups (DlNN; DLNO; LDNN; LDNO, LONN; LONO; DANN; and DANO). The cockerels were subjected to fattening test and egg production of pullets was recorded following the procedure as in the parent generation. Results from fattening test in the parent generation indicated that the Dahlem both normal feathered and naked neck had higher body weight at hatch than the local fowl. At 12 weeks of age, the Dahlem naked naked neck males had higher body weight dressed percentage than the Dahlem normal feathered and the indigenous fowl (normal feathered). Traits such as gizzard, head, liver and heart percentage were unimportant since no significant difference were observed among the three-genotype groups. Results from laying test (Parent generation) indicated that the Dahlem Red both naked neck and normal feathered laid eggs than the indigenous fowl. The Dahlem (both naked neck and normal feathered) had higher feed intake and feed efficiency than the indigenous chicken. Indigenous fowl came into lay (Sexual maturity) later than the Dahlem birds but had lower mortality and higher yolk percentage. Eggs of Dahlem layer had higher albumen and yolk height than that of the local fowl. No differences were observed among genotypes for yolk colour, shell percentage and egg breaking strength. Indigenous hens had higher abdominal fat percentage than the Dahlem hens. Results on body weight in the first generation, revealed that Dahlem naked neck chicks had body weight at hatching. Local x Dahlem naked neck crossbreds had highest 12 weeks body weight and carcass yield. Heterosis for 12 weeks body weight was positive in both naked neck and normal feathered type. Local x Dahlem crossbreds, both normal feathered and naked neck types had higher 12 weeks body weight than its reciprocal cross. Results on egg production performance (G1) revealed that local x Dahlem crossbreds produced highest number of eggs (233 eggs) than local naked neck (142 eggs). Dahlem normal feathered hens produced higher egg mass (12.8kg) than local naked neck hens (6.7 kg). Highest feed consumption was observed for in the Dahlem normal feathered genotype group (0.27) and it was lowest for local naked neck genotype group (0.16). Crossbreds attained earkier sexual maturity than the pure breeds. Positive heterosis was observed for egg number and egg mass in both naked neck and normal feathered genotypes. Normal feathered local x Dahlem crossbreds produced higher egg number than its reciprocal cross but it was reverse for the naked neck type. Similar pattern was observed for egg mass also. Difference in feed efficiency was not found between reciprocal crosses of normal feathered types while local x Dahlem crossbred had higher feed efficiency among the naked neck type. An appreciable improvement in body weight and egg production traits was observed on crossing ICF with German Dahlem Red. Positive heterosis was observed for body weight in cockerels, egg number and egg mass. Reciprocal effects were variable between the normal feathered and naked neck genotypes for most of the traits. Effect of necked neck gene was consistent in improving body weight, carcass yield and egg weight.